Pelatihan Public Speaking pada Remaja Karang Taruna Desa Tanjung Tambak Baru - Mutia Mawardah; Yogi Yogi (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
Public speaking is an important skill for every person and organization to have. Doing public speaking requires thorough practice to get used to conveying a topic in front of many people. However, in reality, many people and young people have low public speaking skills, which makes it difficult for them to express their opinions in front of many people, so public speaking training was held for this youth group so that participants taking part in the training understand the importance of having public speaking skills and how to improve these skills. Apart from that, public speaking training is needed in youth organizations so that in internal and external communication there is no miscommunication and conveying opinions. The method used in this activity is public speaking training through stand up comedy. Based on the evaluation questionnaire, the Pre-Test and Post Test that were given to 15 training participants showed very good results. Based on the post-test completed by 15 people, there were 10 people who got good results with a score of 76-100, only 2 people got a score of (56-75). This shows a lot of improvement from the previous pre-test results, where only 3 people got good scores.